Pola penggunaan obat tetes mata pada karyawan IT penderita computer vision syndrome di lingkungan PT. Telekomunikasi Indonesia, Tbk. Cabang denpasar - Dinda Paramaningtyas Sudibya; I Gusti Ayu Artini; I Gusti Made Aman (E-Jurnal Medika Udayana, 2018)
Generally 80% office works are done using computers, although computer usage actually can lead to some problems. The collective physical disorder suffered by computer users are called Computer Vision Syndrome (CVS), which also suffered by approximately 88-90% computer users. The aim of this study was to define eye drops usage pattern in IT staffs in Denpasar office branch of PT. Telekomunikasi Indonesia, Tbk who suffer CVS. Descriptive cross-sectional is the method used in this research by doing direct observation, and also using questionnaire as the medium given to study subject who met the inclusions and exclusions criterion. Data from study subject then proceed using SPSS for descriptive statistic. From 60 patients who met the criterion, 40 subjects (66.7%) suffer CVS. According to the education level, we found the highest number in subject with good knowledge (51.7% in CVS group and 25% in non-CVS group). According to the eye condition, researchers found that 21 (35%) subjects in CVS group have good behavior, also in non-CVS subjects (18.3%). According to the regularity of eye drops usage, we found the highest number in “regular enough” category (58.3%) and the lowest in “very regular” (3.3%) in CVS group, while in non-CVS group, the highest was found in “regular enough” (28.3%) and the lowest in “less regular” (5%). According to the eye drops usage patterns, we found the highest number in “good” category (38.3%) for CVS group, while in non-CVS group was in “less” category (25%). Incident prevalence of CVS in this study was different with the previous study and probably this is because of the purposive sampling performed in this study. Study subject in this study were majority have a high education background, therefore this also affected subject’s behavior towards eye health, regularity and pattern of eye drops usage. Keywords: Computer Vision Syndrome (CVS), computer, eye drops